2011
DOI: 10.1186/1471-2474-12-256
|View full text |Cite
|
Sign up to set email alerts
|

Generation of subject-specific, dynamic, multisegment ankle and foot models to improve orthotic design: a feasibility study

Abstract: BackgroundCurrently, custom foot and ankle orthosis prescription and design tend to be based on traditional techniques, which can result in devices which vary greatly between clinicians and repeat prescription. The use of computational models of the foot may give further insight in the biomechanical effects of these devices and allow a more standardised approach to be taken to their design, however due to the complexity of the foot the models must be highly detailed and dynamic.Methods/DesignFunctional and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The key sources of errors in estimating , and signals for each class of methods are: Kinematics-based methods: (1) these methods rely on a dynamic human model to estimate , and signals. It has been shown that the accuracy of the estimated signals is very sensitive to the characteristics of the human model such as foot [ 106 ] and knee joint [ 107 ] models. This can be a source of significant uncertainty in the accuracy of the model outputs; (2) errors in measured kinematic data, particularly errors in the measured orientations in the case of using wearable IMUs [ 108 ]; (3) the simplifying assumptions used in body dynamic model and the inverse dynamics analysis, such as solid body segments and frictionless joints; (4) the inaccuracies in anthropometric data, particularly the size, density and weight of body segments, the location of joint centres and the location of centre of mass of each body segment; (5) soft tissue artefacts (STA) [ 109 , 110 ]; and (6) inherent computational errors of the methods proposed to solve the indeterminacy problem of the closed-kinematic chain during DSP.…”
Section: Discussionmentioning
confidence: 99%
“…The key sources of errors in estimating , and signals for each class of methods are: Kinematics-based methods: (1) these methods rely on a dynamic human model to estimate , and signals. It has been shown that the accuracy of the estimated signals is very sensitive to the characteristics of the human model such as foot [ 106 ] and knee joint [ 107 ] models. This can be a source of significant uncertainty in the accuracy of the model outputs; (2) errors in measured kinematic data, particularly errors in the measured orientations in the case of using wearable IMUs [ 108 ]; (3) the simplifying assumptions used in body dynamic model and the inverse dynamics analysis, such as solid body segments and frictionless joints; (4) the inaccuracies in anthropometric data, particularly the size, density and weight of body segments, the location of joint centres and the location of centre of mass of each body segment; (5) soft tissue artefacts (STA) [ 109 , 110 ]; and (6) inherent computational errors of the methods proposed to solve the indeterminacy problem of the closed-kinematic chain during DSP.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the generation of an anatomically detailed 3D model of a foot from imaging data is a time and labour intensive process and is not feasible for individual patients. Approaches using template models that can be parametrically scaled to match the foot anatomy of different individuals based on simpler measurements have been suggested [48] . This may be a more feasible approach but it remains to be fully realised.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the data capturing of the measurements in this article have been published before [ 15 ]. This section gives a brief overview of the measurements performed to acquire input data for the kinematic model.…”
Section: Methodsmentioning
confidence: 99%
“…The model was driven using motion capture data from all participants, three trials for each subject. A previously described marker protocol with 43 markers on the lower extremities was used [ 15 ]. The marker data was used to calculate joint angles in a kinematic analysis of an over-determinate system [ 17 ].…”
Section: Methodsmentioning
confidence: 99%